2009
DOI: 10.1002/qre.1069
|View full text |Cite
|
Sign up to set email alerts
|

Reducing mold changing time by implementing Lean Six Sigma

Abstract: Six Sigma is a well-structured methodology that focuses on reducing variation, measuring defects and improving the quality of products, processes and services. Lean Production is an approach that focuses on reducing the cycle time and eliminating waste in processes. Combining the principles of Six Sigma and Lean can achieve synergistic results that neither system can achieve alone. This paper presents a case study at a printed circuit board company in China illustrating how the company effectively applied a Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 18 publications
0
36
0
1
Order By: Relevance
“…The seven wastes are: motion, overproduction, over processing, lead time, rework, inventory and defects (Chakravorty and Shah, 2012;Lee and Wei, 2009;Bhuiyan et al, 2006;Vinodh et al, 2011). In addition, two more types of waste have appeared in literature recently as stated by Vinodh et al (2012): underutilization of people's creativity and environmental waste.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The seven wastes are: motion, overproduction, over processing, lead time, rework, inventory and defects (Chakravorty and Shah, 2012;Lee and Wei, 2009;Bhuiyan et al, 2006;Vinodh et al, 2011). In addition, two more types of waste have appeared in literature recently as stated by Vinodh et al (2012): underutilization of people's creativity and environmental waste.…”
Section: Introductionmentioning
confidence: 99%
“…Lean also focusses on reduction of total cycle time (Drohomeretski et al, 2013;Lee and Wei, 2009) and reduction of lead time (Hu et al, 2008;Chen et al, 2010). Lean consists of many tools and techniques for improvement such as the Kanban system, 5S, Cause and Effect analysis (C&E), Value Stream Mapping (VSM) and many others (Drohomeretski et al, 2013;Chen and Lyu, 2009;Thomas et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A similar approach proposed by Lee and Wei [20] relates the application of LSS to reduce mold changing time. Their combined methodology adopts Six Sigma and Lean tools simultaneously.…”
Section: Lean Six Sigma (Lss) Combination a Literature Reviewmentioning
confidence: 99%
“…The integration of lean six sigma can create a dramatic improvement rather than when lean or six sigma is used separately [16]. This integration can reduce cost, time and improve quality and organisational performance [4], [6]. Lean six sigma will lead to synergies for quality improvement in industry and promote the combination of human and process aspects as a part of process improvement that it will reinforce each other simultaneously [11], [17].…”
Section: A Review Of Lean Six Sigmamentioning
confidence: 99%
“…Aggogeri and Mazzola [3] showed that the combination of lean six sigma could increase the performance level of a manufacturing system in particular a significant result in reduction of costs of poor quality, increasing process cycle efficiency and also increasing process capability. Lee and Wei [4] mentioned that the combination of lean and six sigma concept at PCB manufacturing industry would recognise key process input variables which would result in reducing the variance of mold changing process and time. Dario et al [5] presented an application model of the lean six sigma DMAIC to improve manufacturing process that has a significant result in reducing costs saving on raw material.…”
Section: Introductionmentioning
confidence: 99%